The rise and fall of a transderivational constraint: the case of Malay - Farid M. Onn.,; Becker, Lee A. (Universiti Kebangsaan Malaysia, 1977)
In this paper we will present evidence supporting the existence of a phonological transderivational constraint. We will discuss the manner in which it was eliminated, and why individual morphemes were treated differently. We will compare this example with several proposed syntactic and morphological transderivational constraints and note their common function: avoidance of ambiguity. Finally, we will discuss the hypothesis of a universal characterization of when potential ambiguity is not tolerated and describe one type of example which, if found, could readily shows that this hypothesis is false.